Metamorphosis of resistance tracing the evolution of the pulahanes de Passi, Iloilo from a revolutionary to a religious group. - Gonzales, Rey Carlo T.
The research studies the transformation of the Pulahanes de Passi, originally a revolutionary group which had ties to the Katipunan under Aguinaldo into the BUlahanes, a religious group. The questions raised involed finding out what institutions/religions influenced the Pulahanes de Passi as revolutinary group, and how those influences affectedly changed Pulahanes into Bulahanes., The Linear apporach was utilized to emphasize the progressive effect of the different institutions/religions in transforming the Pulahanes de passi into Bulahanes. Information was gathered via the study written sources and via oral interviews with residents of the area, the Pulahanes, relatives, and people who have come across them in the past. The researcg findings pointed out that indeed the revolutionary Pulahanes of Passi (ca. 1890s) evolved into the religious Bulahanes (ca. 1930s), the former very much dissimilar tot he latter. This evolution could be attributed to the different institutions/religions that influenced the Pulahanes (Masonry, animism, Catholicism, and Protestantism) and the events in our history (the Philippine Revolution and the Filipino-American War) that catalyzed their evolution. This catalysis was the result of the response of the Pulahanes to the circumstances surrounding them. The coming of the Americans and their successful pacification of the Filipinos became the primary factor for the transformation of the Passinhon group from Pulahan to Bulahan.